Pengembangan Model TPSR untuk Meningkatkan Kolaborasi dan Heutagogy Peserta Didik dalam Pembelajaran PJOK SMP - Susanto, Ermawan; Subagyo, Subagyo; Tirtawirya, Devi; Irmansyah, Johan (Discourse of Physical Education, 2026)
Twenty-first-century physical education should develop students’ responsibility, collaboration, and self-determined learning; however, learning models integrating these aspects remain limited. This study aimed to develop a responsibility learning model based on Teaching Personal and Social Responsibility (TPSR), integrated with collaborative skills and heutagogical principles in junior high school physical education. The study employed a Research and Development method using the ADDIE model. The participants included physical education teachers, expert validators, and 60 eighth-grade students. The instruments consisted of a needs-analysis questionnaire, focus group discussion guidelines, expert validation sheets, observation sheets, and the TARE instrument. Data were analyzed using Aiken’s V, CFA, construct reliability, percentages, and a paired sample t-test. The results showed that the model was valid, practical, and effective. Students’ responsibility scores increased from 2.7384 to 3.2243, with t = 6.8575 and p < .001. The model also supported collaborative behavior and learner autonomy.